SYMBOLIC PATTERNS AT GEORGE FLOYD'S DEATH DEMONSTRATIONS: A LINGUISTIC LANDSCAPE STUDY - Bahy Chemy Ayatuddin Assri (Leksema: Jurnal Bahasa dan Sastra, 2021)
This article was aimed at revealing the symbolic patterns behind the demonstrations on George Floyd’s death in the United States. The death due to an abusive treatment of a police officer to the black person has resulted in public demonstrations across the country. Before the case, however, there have been numerous acts of racism to black people and it has been common in the United States. Some Americans still believe that white people is superior to black people. They resist the existence and development of black people’s culture by violating and discriminating black people rights in any circumstances. A research result has shown that black people are likely prone to death than the white ones. To study the symbolic patterns of the demonstrations, the researcher used Charles Sanders Pierce’s semiotic theory. Additionally, linguistic landscape approach was also employed since te analysis involved the use of language in public spaces as a marker of human interactions in society. The method for analysis was descriptive-qualitative whose the textual data were collected from different online news media. The result shows that there were two dominant symbolic patterns coming from the demonstrations, namely justice and satire patterns.  The former demanded fair treatments to black people whereas the latter  accused the police as the mastermind of all the violence and discrimination to black people.